THE INFLUENCE OF ELECTRONIC WORD OF MOUTH (E-WOM) ON INTEREST IN VISITING TOURISM POSTS ON @SOALPALU ACCOUNTS FOR TADULAKO UNIVERSITY STUDENTS - Aditya Sumanegara; Rizqy Alfiyaty; Dwi Rohma Wulandari (LPPM Universitas Tadulako, 2022)
This study aimed to determine the effect of intensity, valance of opinion, and content in E-WOM on student visiting interest in tourism posts on @soalpalu accounts. The sampling technique used quota sampling technique using the Slovin formula, a sample of 100 respondents was used. The analysis tool uses multiple linear regression, using the classical assumption, F, and t-test tests. Based on the results of the classical assumption test, the data is normally distributed, the F test shows that simultaneously the independent variable (x) affects the dependent variable, and the t-test shows that all variables (x) partially affect the interest in visiting (y). The results of this study are: 1) Intensity variable has a positive and significant effect on visiting interest in @soalpalu account tourism posts with a significance value of 0.00 <0.05. this shows that the intensity of @soalpalu is high among students so it has a positive influence on visiting interest. 2) The valance of the opinion variable has a positive and significant effect on visiting interest in @soalpalu account tourism posts with a significance value of 0.009 <0.05. This shows that positive opinions and good recommendations are obtained by students so that they have a positive effect on visiting interest. 3) The content variable has a positive and significant effect on visiting interest in @soalpalu account tourism posts with a significance value of 0.00 <0.05. This result shows that the content @soalpalu contains information that clearly describes the condition of interesting tourist objects, which affects students' interest in visiting. 4) simultaneously intensity, valance of opinion, and content in E-WOM affect the interest in visiting tourism posts on the @soalpalu account with a significance value of 0.000> 0.05.